2016
DOI: 10.1038/srep25338
|View full text |Cite
|
Sign up to set email alerts
|

Early life stress affects limited regional brain activity in depression

Abstract: Early life stress (ELS) can alter brain function and increases the risk of major depressive disorder (MDD) in later life. This study investigated whether ELS contributes to differences in regional brain activity between MDD patients and healthy controls (HC), as measured by amplitude of low-frequency fluctuation (ALFF)/fractional (f)ALFF. Eighteen first-episode, treatment-naïve MDD patients and HC were assessed with the Childhood Trauma Questionnaire and resting-state functional magnetic resonance imaging. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 43 publications
0
20
0
3
Order By: Relevance
“…ALFF also helps to avoid the potential bias induced by selection of the ‘seed’ voxels or the number of components in resting-state functional connectivity analysis 24 , 26 such as graph theory, ROI-to-ROI matrix analysis, seed-to-voxel analysis and independent component analysis. Resting-state studies in MDD have reported increased ALFF in the frontal cortex, including ACC, OFC 27 , 28 and posterior cingulate cortex/precuneus 29 , as well as the fusiform gyrus 29 31 and lingual gyrus 30 , 32 , which have been thought to reflect the excessive self-referential processing of MDD. Decreased ALFF has been reported in the cerebellar hemispheres 33 , 34 and superior temporal gyrus 32 , 35 , and this has been linked to deficits in cognitive control of emotional processing.…”
Section: Introductionmentioning
confidence: 99%
“…ALFF also helps to avoid the potential bias induced by selection of the ‘seed’ voxels or the number of components in resting-state functional connectivity analysis 24 , 26 such as graph theory, ROI-to-ROI matrix analysis, seed-to-voxel analysis and independent component analysis. Resting-state studies in MDD have reported increased ALFF in the frontal cortex, including ACC, OFC 27 , 28 and posterior cingulate cortex/precuneus 29 , as well as the fusiform gyrus 29 31 and lingual gyrus 30 , 32 , which have been thought to reflect the excessive self-referential processing of MDD. Decreased ALFF has been reported in the cerebellar hemispheres 33 , 34 and superior temporal gyrus 32 , 35 , and this has been linked to deficits in cognitive control of emotional processing.…”
Section: Introductionmentioning
confidence: 99%
“…Of note, MDD subjects exhibited decreased fALFF in multiple areas of the right PFC in the present study. The PFC areas have been most consistently identi ed as being closely related to MDD [35,36], and each distinct subregion of the PFC plays a different critical role in the cognitive bias of MDD [30]. The altered PFC regions in our study mainly consisted of the dorsal lateral prefrontal cortex (DLPFC), ventrolateral prefrontal cortex (VLPFC) and the premotor areas.…”
Section: Discussionmentioning
confidence: 79%
“…Figure 1 shows a flow diagram of the study selection process. 12 papers (Liu et al, 2010, 2013, 2014; Peng et al, 2011; Chen J. D. et al, 2012; Shen et al, 2014; Wang L. et al, 2014, 2016; Wang L. J. et al, 2014; Zhang et al, 2014; Lai and Wu, 2015; Du et al, 2016) were selected. Specifically, this meta-analysis involved 313 medication-naive patients with first-episode unipolar MDD (55.6% females; mean age 31.62 years) from China, matched with 283 HCs (51.9% females; mean age 30.77 years) based on age, sex, education and nationality.…”
Section: Resultsmentioning
confidence: 99%
“…The amygdala is a key structure in a limbic circuit and plays an important role in involuntary, automatic appraisal processes, which are crucial components of emotion (Dannlowski et al, 2007). The amygdala is likely involved in the pathophysiology of depression, because several studies have used various imaging modalities, such as structural MRI (Lorenzetti et al, 2010; Burke et al, 2011), task-related MRI (Thomas et al, 2001) and rs-fMRI (Du et al, 2016), to report amygdala alterations in patients with depression. Previous meta-analyses (Campbell et al, 2004; Arnone et al, 2012) have reported the lack of volume differences in the amygdala between patients with depression and HCs.…”
Section: Discussionmentioning
confidence: 99%